The Sound Shifting of British English Accent: A Phonological Analysis - Ambalegin, Ambalegin; Handayani, Nurma Dhona (IdeBahasa, 2023)
This research aims at identifying the English words pronounced by the Brits which did not follow the standard of Received Pronunciation (RP). The received Pronunciation is proposed by Finegan (2015). The specific sound shifting taken becomes the accents of British English. These accents were sometimes used by the EFL learners while speaking English as they thought it was the standard English. This qualitative research took the data from the English speeches spoken by the famous Brits on YouTube. This research applied the observational method to collect the data, and phonological approach, identity method, and articulatory phonetic identification to analyze the data. It is summed up that the glottal stop [ʔ] replaces the alveolar [th] at the final and between vowels. The dental [θ[ and [ð] are shifted by the labiodental [f] and [v]. The velar [x] replaces the velar [k], the final velar [ŋ] becomes [n], and the final [th] is shifted by the glottal [h]. In the case of vocalization, the diphthong [eɪ] becomes [aɪ], the vowel [æ] becomes [ʌ], the schwa [ə] becomes [æ], and the vowel [ʌ] becomes [ʊ]. These changes are not for the British English in general. The accents depend on the regions where the speakers come from. However, the glottal stop [ʔ] are almost used by the speakers. This finding gives information that these accents are not the standard English. Moreover, these British English accents are not the mistakes.